Lactoferrin: A Nutraceutical with Activity against Colorectal Cancer - Ramírez-Rico, Gerardo; Drago-Serrano, Maria Elisa; León-Sicairos, Nidia; de la Garza, Mireya (Frontiers in Pharmacology, 2022)
Homeostasis in the human body results from the tight regulation of several events, since too little inflammation disrupts the process of tissue repair and remodeling, whereas too much exerts a collateral effect by causing tissue damage with life-threatening consequences. In some clinical conditions, such as inflammatory bowel disease (IBD), inflammation functions as a double-edged sword by either enabling or inhibiting cancer development and progression. Generally, cancer develops through evasion mechanisms that regulate cell growth, causing a high rate of uncontrolled proliferation, and mechanisms for evading cell death, such as apoptosis. Moreover, chronic inflammation is a factor that contributes to colorectal cancer (CRC), as observed in individuals with IBD; all these conditions favor an increased rate of angiogenesis and eventual metastasis. Lactoferrin (Lf) is a mammalian iron-binding multifunctional glycoprotein regarded as a natural compound that up- and downregulates both humoral and cellular components of immunity involved in regulating the inflammatory response and maintaining gut homeostasis. Human and bovine Lf share high sequence homology and have very similar antimicrobial, anti-inflammatory, and immunomodulatory activities. Bovine Lf from milk is considered a safe molecule and is commercially available in large quantities. This review mainly focuses on the regulatory effects of orally administered bovine Lf on the inflammatory response associated with CRC; this approach indicates that CRC is one of the most frequently diagnosed cancers and affects the intestinal tract with high clinical and epidemiologic relevance. Thus, this review may provide foundations for the potential use of bovine Lf alone or as a natural adjunct agent to increase the effectiveness and reduce the side effects of anticancer chemotherapy.